Effect of Non-Inertial Acceleration on Thermal Convection in an Anisotropic Porous Medium with Temperature-Dependent Darcy and Brinkman Frictions (Global Journal of Science Frontier Research, 2018)
A linear stability analysis is performed for monodiffusive rotating porous medium with temperature obtain the eigen value of the problem. The effect of and the other parameters of the problem is considered for both stationary convection in the presence and absence of parameters' influence on convection in the presence of rotation, for both rates, are presented. Low-porosity viscosity liquids.
Keywords: anisotropy; rotation; porous medium; variable viscosity; thermal convection